East German intellectuals and public discourses in the 1950s: Wieland Herzfelde, Erich Loest and Peter Hacks - van der Wall, Hidde Tjakke (2014)
The aim of this thesis is to contribute to a differentiated reassessment of the cultural history of the German Democratic Republic (GDR), which has hitherto been hampered by critical approaches which have the objective of denouncing rather than understanding East German culture and society. Approaches such as these rely on schematic black-and-white oppositions, e.g. the dichotomy of conformity and dissidence, and present the East German cultural public spheres in a top-down way as a closed space in which a supposedly monolithic and deceitful Party ideology dictates what can be said or written. In order to reconceptualise these oversimplifying models, this thesis analyses public discourses from below, focusing on case studies of three public intellectuals with very distinct profiles: Wieland Herzfelde (1896-1988), Erich Loest (1926-2013), and Peter Hacks (1928-2003). Based on published as well as archival sources, this thesis examines their contributions to the plurality of public discourses in East Germany, concentrating on the 1950s as the most heavily contested decade of German division and the Cold War, both of which put great pressure on intellectuals. Whereas research has traditionally regarded these three intellectuals as having either a dissident or a conformist profile, this thesis argues that their attitudes were too ambiguous and the dilemmas they faced too complex to be reduced to such a clear-cut, schematic template.